Analysis Of Parents Knowledge To Giving Behavior Sex Education For Teenage Girl - Siswanti (Journal of Applied Nursing and Health, 2019)
Free sex in adolescents can be interpreted as a variety of risky teen behaviors. Understanding of sexuality is considered taboo by society and the existence of erroneous myths about sex causes teenagers' understanding of sexuality knowledge to be low. The importance of parental knowledge towards the provision of sex education to adolescents to prevent unwanted behavior. The aim is to find out whether there is a relationship between Parent Knowledge and Sex Education Giving Behavior for Young Women in Tutuyan 3 State Junior High School, Bolaang Mongondow Regency, East Sulawesi Province. The design used in the study was Cross Sectional. The population is all parents who have young women in the 3 Public Schools in Tutuyan, East Bolaang Mongondow Regency, North Sulawesi Province. The sample size is 60 respondents using Independent Variable Purposive sampling technique research is Knowledge about sex education in parents. Dependent variable is educational sex behavior for parents. Data was collected using a questionnaire, then the data were analyzed using the Spearmant rho test with a significance level of α ≤ 0.05. The results showed that half of respondents had enough knowledge as many as 30 respondents (50%), positive behavior as many as 47 respondents (78.3%), statistical tests in this study using the spearmant rho test with a <0.05 obtained p = 0,000 where H1 is accepted and H0 is rejected, which means that there is a relationship between Parent Knowledge and Sex Education Giving Behavior for Young Women in Tutuyan 3 State Junior High School, Bolaang Mongondow Timur Regency, North Sulawesi Province. There is a relationship between Parents' Knowledge and Sex Education Giving Behavior for Young Women in Tutuyan 3 State Junior High School, Bolaang Mongondow Timur Regency, North Sulawesi Province.